COVID-19-mandated social restrictions unveil the impact of social time pressure on sleep and body clock - Maria Korman (Nature Portfolio, 2020)
Abstract In humans, sleep regulation is tightly linked to social times that assign local time to events, such as school, work, or meals. The impact of these social times, collectively—social time pressure, on sleep has been studied epidemiologically via quantification of the discrepancy between sleep times on workdays and those on work-free days. This discrepancy is known as the social jetlag (SJL). COVID-19-mandated social restrictions (SR) constituted a global intervention by affecting social times worldwide. We launched a Global Chrono Corona Survey (GCCS) that queried sleep–wake times before and during SR (preSR and inSR). 11,431 adults from 40 countries responded between April 4 and May 6, 2020. The final sample consisted of 7517 respondents (68.2% females), who had been 32.7 ± 9.1 (mean ± sd) days under SR. SR led to robust changes: mid-sleep time on workdays and free days was delayed by 50 and 22 min, respectively; sleep duration increased on workdays by 26 min but shortened by 9 min on free days; SJL decreased by ~ 30 min. On workdays inSR, sleep–wake times in most people approached those of their preSR free days. Changes in sleep duration and SJL correlated with inSR-use of alarm clocks and were larger in young adults. The data indicate a massive sleep deficit under pre-pandemic social time pressure, provide insights to the actual sleep need of different age-groups and suggest that tolerable SJL is about 20 min. Relaxed social time pressure promotes more sleep, smaller SJL and reduced use of alarm clocks.